Analysis of Socio-Scientific Issues in Chemistry Textbooks for Form IV and V in Malaysia - Fadhila Nisaulmuna; Antuni Wiyarsi (Universitas Negeri Yogyakarta, 2024)
Malaysia as one of the countries that has integrated STEM in its education curriculum has a close relationship with SSI-based learning. Students' understanding of SSI is influenced by all important components in supporting the implementation of the learning process, one of which is the textbook. This study aims to compare the number of occurrences of SSI topics based on the level and stage of presentation between level IV and V chemistry textbooks in Malaysia. This qualitative research uses documentary method with descriptive content analysis design. A total of 2 level IV and V textbooks were selected using purposive sampling as data sources. The instrument used was a tabular coding analysis sheet consisting of two focuses of study, namely the level and stage of presentation. The coding results were then analyzed using the delphi technique with 2 expert lecturers. The findings in this study revealed that the number of SSI occurrences in chemistry textbooks level IV and V in Malaysia in terms of topics was 71 data. The book that has a higher occurrence of SSI topics is level IV chemistry textbooks. The number of SSI occurrences in terms of the most presentation stages as material is 37 data, the presentation level in the form of N/A is 41 data, from the global SSI aspect is 51 data, from the chemical concept is 141 data, from the SSI dimension is 213 data, and in terms of other chemical concept mapping is 93 data.